2001
DOI: 10.1021/om991019h
|View full text |Cite
|
Sign up to set email alerts
|

Metallathiirenes. 3.1 Thiocarbamoyl and Alkoxythiocarbonyl Complexes of Molybdenum(II) and Tungsten(II)

Abstract: Synthetic routes to thiocarbamoyl (thiocarboxamide) complexes of divalent molybdenum and tungsten are reported: The reaction of fac-[Mo(CO) 3 (NCMe) 3 ] with N,N-dimethyl thiocarbamoyl chloride (Me 2 NC(dS)Cl) at low temperature provides a thermally labile intermediate (1) presumed on the basis of subsequent transformations to be [Mo(η 2 -SCNMe 2 )-Cl(CO) 3 (NCMe)]. Reactions of 1 with K[HB(pz) 3 ] (pz ) pyrazol-1-yl), NaC 5 H 5 , bipy, or tmeda provide the complexes [Mo(η 2 -SCNMe 2 )(CO) 2 {HB(pz 4), and [Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…The starting material [Mo(g 3 -C 3 H 5 )(Br)(CH 3 CN) 2 (CO) 2 ] (labeled 5 in Scheme 1) was prepared by a slight modification of the method reported in literature [25], whereas the preparation of compound 6 followed the literature method [26]. After dissolving 5 in acetonitrile, PPh 3 was added to the yellow solution with stirring, and compound 6 was obtained as a yellow precipitate after heating under reflux for 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The starting material [Mo(g 3 -C 3 H 5 )(Br)(CH 3 CN) 2 (CO) 2 ] (labeled 5 in Scheme 1) was prepared by a slight modification of the method reported in literature [25], whereas the preparation of compound 6 followed the literature method [26]. After dissolving 5 in acetonitrile, PPh 3 was added to the yellow solution with stirring, and compound 6 was obtained as a yellow precipitate after heating under reflux for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Trimethylphosphine [32] and [Mo(CH 3 CN) 2 (CO) 2 (PPh 3 ) 2 ] (compound 6) [26] were prepared according to literature methods.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of complex [Mo(CO) 2 (h 2 -SCNMe 2 )-(PPh 3 ) 2 Cl] 1, with NH 4 S 2 P(OEt) 2 in dichloromethane at room temperature resulted in the chloride and triphenylphosphine displaced seven coordinated diethyldithiophosphate thiocarbamoyl-molybdenum complex, 13 The air-sensitive orange compounds b-3 and 4 are soluble in dichloromethane and ace-tonitrile, slightly soluble in methanol, and insoluble in diethyl ether and n-hexane.…”
Section: Resultsmentioning
confidence: 99%
“…7 Thiocarbamoyl Mo and W (VIB) complexes are known. [8][9][10][11] Our previous report 12 has shown that reaction of the thiocabamoyl-molybdenum complex [Mo(CO) 2 (h 2 -SCNMe 2 )(PPh 3 ) 2 Cl] 13 with pyridine-2-thionate, C 5 H 4 NS -, in dichloromethane at room temperature, yields the seven coordinated pyridine-2-thionate thiocabamoyl-molybdenum complex [Mo(CO) 2 (h 2 -SNC 5 H 4 )(h 2 -SCNMe 2 )(PPh 3 )] a-2. In complex a-2, the triphenylphosphine ligand and one carbonyl ligand are in the trans position.…”
Section: Introductionmentioning
confidence: 99%
“…For O-Aryl thiocarbonate, benzoxazoline-2-thione, chromene-2-thione and N,N-dimethylthiocarbamate metal complexes, see: Chen et al (1978); McFarlane et al (1998); Zheng et al (2006) and Zhang & Shi (2004), respectively. For phenoxylcarbonyl metal complexes, see: Anderson et al (2001). We are interested in the synthesis of dithiocarbamate, pyridine-2-thionate and N,N-dimethyldithiocarbarmoyl metal complexes.…”
Section: Related Literaturementioning
confidence: 99%